(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The article deals with the subject of exile and forced displacement in Algeria during the period of the French occupation, a study through contemporary Algerian historical writings 1871-1900 , which dealt with the subject of exile and forced displacement at intervals, especially after the end of the Mokrani revolution and the beginning of those unfair trials to deport them from their original homeland to eliminate popular resistances and on the one hand to facilitate the settlement of centenarians in their place, and the intervention also addresses the subject of exile and forced displacement from A legal perspective in order to prove the French crime against the Algerians, then the reasons and objectives of exile and displacement outside the homeland after the resistance of Mokrani, followed by the presentation of selected models of Algerian historical writings that dealt with the subject, and this by describing the version, its owner, then its content, and then the historical addition provided by these writings to the subject of exile and displacement. The intervention stems from a major problem: How did contemporary Algerian historical writings deal with the issue of Algerian exiles and forcibly displaced persons? The intervention aims to reveal the daily life of the exiled Algerians through these writings, and to know their sizes and suffering outside the motherland due to the policy of the French occupation, and the intervention depends on the critical analytical approach due to the nature of the subject.